Ancora sul procedimento di stipulazione delle intese tra Stato e confessioni religiose diverse dalla cattolica (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Ulteriori riflessioni su un tema controverso - 2. Intese e procedimento amministrativo - 3. La fase di accesso alle trattative - 4. Le trattative e la sottoscrizione dell’intesa - 5. L’iniziativa legislativa e l’iter legislativo di sottoscrizione dell’intesa - 6. Le conseguenze di regime - 7. Conclusioni.Again about the procedure of stipulation of the agreements (ʻinteseʼ) between the State and the religious denominationsABSTRACT: The essay focuses on the topic of the agreements which should be subscribed by the Italian Government and the representatives of the religious denominations, in compliance with the article 8, c. 3, of the Italian Constitution. In a recent and highly controversial judgement, the Constitutional Court has recognised that the act of selection of the denominations for the negotiations aimed to the subscription of such agreements has the nature of a ʻpolitical actʼ and could therefore not be reviewed by any judges of the Country. The judgement has been deeply criticized by the most of the Italian scholars specialized in the subject. The object of this essay is to demonstrate that at least some parts of the complex procedure of production of the above mentioned agreements could not be considered ʻpoliticalʼ, in the technical sense, but should rather be reduced to the model of the typical administrative procedure. In that case, the Government acts of selection and of withdrawal from the negotiations could be object of a common administrative judicial review.